THE PHENOMENON OF MONEY POLITICS PRACTICES IN THE DIRECT ELECTION OF VILLAGE HEADS IN SUMBEREJEO VILLAGE, BONANG SUB-DISTRICT, DEMAK DISTRICT IN 2023 - Sarifudin, Muhammad; Faozi, Safik (Jurnal Meta-Yuridis, 2024)
The formulation of the problem in this study is "How does the process of the phenomenon of money politics practice occur in the election of the Village Head in Sumberejo Village, Bonang District, Demak Regency? and What are the factors that cause the phenomenon of money politics practices in the election of Village Heads in Sumberejo Village, Bonang District, Demak Regency?". The research method used in this study is Sociological Juridical, which is research that explains the phenomenon of money politics practice in the 2023 Sumberejo village head election with primary data and secondary data, namely primary data through interviews and secondary data through literature studies. The results of this study explain that the process of the phenomenon of money politics practice occurs during the candidacy or registration stage and during the campaign or election stage. Where at the registration or candidacy stage, it was found that money was given in the amount of Rp. 50,000 and at the campaign or election stage, it was found that the money giver was approximately in the range of Rp. 150,000 â€“ Rp 200,000.Â  Of the three candidates who registered, there were 2 candidates who practiced money politics. The factors that affect the cause of the practice of money politics are due to the educational factor, namely the lack of public understanding of the meaning of the village head election. In addition to education, there is also an economic factor because the average economy of the people of Sumberejo Village is lower class, where the election of the village head is used as a momentum to receive money from the village head candidate and there is also a cultural tradition or habit factor where the culture of money politics has become a habit and has been rooted since the time the village head election arrived.